Structural Characterization of Magnesium-based Metal-organic Framework Carbon Composites - Kamal, Khaliesah; Azmi Bustam, Mohamad; Mohd Shariff, Azmi; Pré, Pascaline; Hamon, Lomig (International Journal of Psychosocial Rehabilitation, 2020)
A magnesium-based metal-organic framework (MOF), Mg-MOF-74, has been denoted as a landmark of its kind for CO2adsorption owing to its highly porous structure and strong metal adsorptive sites. However, large void spaces in the framework cannot be fully utilized at ambient conditions due to weak surface dispersive forces. For that reason, two carbonaceous agents, multiwalled carbon nanotubes (CNT) and monolayer graphene oxide (GO), were used to enrich the formation of micropores in the original structure. The objective of the study is to characterize the structure of these new nanomaterials. Mg-MOF-74@CNT and Mg-MOF-74@GO composites were synthesized under solvothermal reaction and characterized by FESEM, EDXS, PXRD, and FTIR analysis. Both GO and CNT were introduced into the framework via in-situ synthesis of the ‘bottle-around-ship’ method to form a homogeneous structure with MOF units. The insertion of composing materials was confirmed under FESEM morphological analysis. The profiles of PXRD and FTIR showed that the crystalline structure of Mg-MOF-74 was well preserved and not ruptured by the hybrid agents. Those structural analyses gave information on the nucleation of Mg-MOF-74 crystallites, increment of metal adsorptive sites, synergetic formation of CNT- and GO-MOF, crystallite size distribution, dilatation of crystallites, and coordination of carboxylate ligands.